PENGARUH POPULASI KEMANGI (OCIMUM SP.) SEBAGAI SUMBER REPELLENT TERHADAP PLUTELLA XYLOSTELLA L. (LEPIDOPTERA: PLUTELLIDAE) PADA BUDIDAYA SAWI ORGANIK - Chrisvina Chrisvina; Alam Anshary; Hasriyanty Hasriyanty (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
This study aimed to determine the effect of the population of basil as a repellent plant on the population density of Plutella xylostella in mustard greens. The research was carried out in a coffee plantation Donggala district of Central Sulawesi province in July – September 2019. This study used a Randomized Block design (RBD) method consisting of four treatments with three replicates. The treatments given were monoculture mustard cultivation (T0), population of six basil plants with spacing 70 × 70 cm grown between mustard plants (T1), population of eight basil plants with spacing 60 × 60 cm grown between mustard plants (T2), and population of 12 basil plants with spacing 50 × 50 cm grown between mustard plants (T3). The basil plants significantly reduced the population and intensity attacks of Plutella xylostella pest on the mustard plants. The T3 treatment had the lowest Plutella xylostella counts, with only three moths discovered, whereas the largest pest populations were seen in the monocultures.